2006
DOI: 10.1063/1.2213607
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Global thermodynamics of hydrophobic cavitation, dewetting, and hydration” [J. Chem. Phys. 123, 184504 (2005)]

Abstract: ARTICLES YOU MAY BE INTERESTED INAssessing the thermodynamic signatures of hydrophobic hydration for several common water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Thus, although many models faithfully reveal the free energy change of the association of two hydrophobic entities, a lot fewer successes have been marked up in regard to accurately determining the enthalpy or entropy changes (first derivatives of the initial experiment). Additionally, success in modeling heat capacity changes (a second derivative of the experiment) has been limited to spherical representations of methane [53][54][55][56].…”
Section: The Hydrophobic Effectmentioning
confidence: 99%
“…Thus, although many models faithfully reveal the free energy change of the association of two hydrophobic entities, a lot fewer successes have been marked up in regard to accurately determining the enthalpy or entropy changes (first derivatives of the initial experiment). Additionally, success in modeling heat capacity changes (a second derivative of the experiment) has been limited to spherical representations of methane [53][54][55][56].…”
Section: The Hydrophobic Effectmentioning
confidence: 99%
“…toronto.edu study. [63][64][65][66][67] Notably, this intriguing phenomenon 68,69 provided rationalization for several otherwise puzzling behaviors of compact unfolded states of proteins, 70 even though such a positive heat capacity change was not predicted by bulk-phase solvent accessible surface area considerations. 49 Indeed, recent atomic ͑explicit-water͒ simulations have shown that nonadditivity is significant for hydrophobic interactions among more than two nonpolar solutes.…”
Section: Introductionmentioning
confidence: 99%